Terror trials: life and law in Delhi's courts - Suresh, Mayur (Thinking from elsewhere, 2023)
An ethnography of terrorism trials in Delhi, India, this book explores what modes of life are made possible in the everyday experience of the courtroom. Mayur Suresh shows how legal procedures and technicalities become the modes through which courtrooms are made habitable. Where India's terror trials have come to be understood by way of the expansion of the security state and displays of Hindu nationalism, Suresh elaborates how they are experienced by defendants in a quite different way, through a minute engagement with legal technicalities.Amidst the grinding terror trials-which are replete with stories of torture, illegal detention and fabricated charges-defendants school themselves in legal procedures, became adept petition writers, build friendships with police officials, cultivate cautious faith in the courts and express a deep sense of betrayal when this trust is belied. Though seemingly mundane, legal technicalities are fraught and highly contested, and acquire urgent ethical qualities in the life of a trial: the file becomes a space in which the world can be made or unmade, the petition a way of imagining a future, and investigative and courtroom procedures enable the unexpected formation of close relationships between police and terror-accused.In attending to the ways in which legal technicalities are made to work in everyday interactions among lawyers, judges, accused terrorists, and police, Suresh shows how human expressiveness, creativity and vulnerability emerge through the law